Reformasi Birokrasi SDM Untuk Mewujudkan Mutu Pendidikan di Pondok Pesantren Al-Munawaroh Tabir Raya - Ahmad Ridwan; Siti Aminah; Siti Khatijah; Asep Saifuddin Chalim (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
The purpose of this study was to determine the condition and management and to know the factors that support and hinder the implementation of human resource management at Al-Munawaroh Tabir Raya Islamic Boarding School. This type of research is qualitative. Data collection techniques are obtained from the results of interviews, observation, and document analysis. The interviews were carried out mainly to the clerics, the mother of the niqi and several santri. Qualitative data analysis techniques: data collection, data reduction, data presentation, and conclusion. The results of the study show that the condition of human resources in Al-Munawaroh Tabir Raya Islamic Boarding School has very visionary kyai. K. H. Lukman Hakim, M.Pd.I has succeeded in cadreing the human resources of the santri to be able to exist in managing and developing the potential needed by pilgrims and has been proven to play a role as an agent of change in the community. Management of human resources through: planning, organizing, directing, and controlling. The supporting factors are the number of santri, teachers are alumni, and the high charisma of the clerics. The inhibiting factor was that santri were accepted without selection, limited funds, and the character of the kiai was irreplaceable.